Mammography image restoration based on a radiographic scattering model from a single projection: Experimental study - Kim, Kyuseok; Park, Soyoung; Kim, Guna; Cho, Hyosung; Je, Uikyu; Park, Chulkyu; Lim, Hyunwoo; Lee, Dongyeon; Lee, Hunwoo; Kang, Seokyoon (Journal of the Korean Physical Society, 2017)
In conventional mammography, contrast sensitivity remains limited due to the superimposition of breast tissue and scattered X-rays, which induces low visibility of lesions in the breast and, thus, an excessive number of false-positive findings. Several methods, including digital breast tomosynthesis as a multiplanar imaging modality, air-gap and slot techniques for the reduction of scatters, phase-contrast imaging as another image-contrast modality, etc. , have been investigated in attempt to overcome these difficulties. However, those techniques typically require a higher imaging dose or special equipment. In this work, as an alternative, we propose a new image restoration method based on a radiographic scattering model in which the intensity of scattered X-rays and the direct transmission function of a given medium are estimated from a single projection by using the dark-channel prior. We implemented the proposed algorithm and performed an experiment to demonstrate its viability. Our results indicate that most of the structures in the examined breast were very discernable even with no adjustment in the display-window level, thus preserving superior image features and edge sharpening.